Hollywood or history? : an inquiry-based strategy for using cartoons to teach topics in elementary and secondary social studies - Roberts, Scott L.; Elfer, Charles J. (Hollywood or history?, 2025)
"In response to the limitations associated with teaching through film, we sought to develop practical lesson ideas that might bridge gaps between theory and practice and assist teachers endeavoring to make effective use of film in their classrooms. One of the more interesting sources of visual media many authors in the previous volumes elected to use as the focus of their lesson plans were cartoons. These lesson plans have been some of the more popular in the series and are often easier to adapt for a variety of grade levels. In conducting research for this volume, we learned that cartoons are an often-used media sources in the classroom. They have similar strengths and weaknesses in not only the teaching of history, but other social studies disciplines as well. While in many cases their intended audience is younger children, people of all ages enjoy cartoons. This makes them useful for teaching students at all grade levels, as well as adults, as there will be immediate buy-in if used as a source of analysis for inquiry-based lessons. As with live action film, we believe cartoons can also serve as a powerful tool in the social studies classroom and if appropriately utilized can foster critical thinking and civic mindedness. The College, Career, and Civic Life (C3) framework, adopted by the National Council for the Social Studies in 2013, represents a renewed and formalized emphasis on the perennial social studies goals of deep thinking, reading and writing. The C3 is comprehensive and ambitious. Moreover, we believe that as teachers endeavor to digest and implement the platform in schools and classrooms across the country, the desire for access to structured strategies that lead to more active and rigorous investigation in the social studies classroom will grow increasingly acute. Our hope is that the present volume might play a small role in the larger Hollywood or History? project of supporting practitioners, specifically teachers of preK-12 social studies disciplines, by offering a collection of 19 classroom-ready lesson designed to foster social studies inquiry through the careful use of selected cartoons"--